PIANO: A Web Server for Pseudouridine-Site (Ψ) Identification and Functional Annotation - Song, Bowen; Tang, Yujiao; Wei, Zhen; Liu, Gang; Su, Jionglong; Meng, Jia; Chen, Kunqi (Frontiers in Genetics, 2020)
Known as the “fifth RNA nucleotide”, pseudouridine (Ψ or psi) is the first discovered and most abundant RNA modification occurring at the Uridine site, and plays a prominent role in a number of biological processes. Thousands of Ψ sites have been identified under different biological contexts thanks to the advancement in high-throughput sequencing technology; nevertheless, the transcriptome-wide distribution, biomolecular functions, regulatory mechanisms and disease relevance of pseudouridylation are largely elusive. We report here a web server PIANO for pseudouridine site (Ψ) identification and functional annotation. PIANO was built upon a high-accuracy predictor that takes advantage of both conventional sequence features and 42 additional genomic features. When tested on six independent datasets generated from four independent Ψ profiling technologies (Ψ-seq, RBS-seq, Pseudo-seq and CeU-seq) as benchmarks, PIANO achieved an average AUC of 0.955 and 0.838 under the full transcript and mature mRNA models, respectively, marking a substantial improvement in accuracy compared to the existing in silico Ψ site prediction methods, i.e., PPUS (0.713 and 0.707), iRNA-PseU (0.713 and 0.712) and PseUI (0.634 and 0.652). Besides, PIANO web server systematically annotates the predicted Ψ sites with post-transcriptional regulatory mechanisms (miRNA-targets, RBP-binding regions and splicing sites) in its prediction report to help the users explore potential machinery of Ψ. Moreover, a concise query interface was also built for 4303 known Ψ sites, which is currently the largest collection of experimentally validated human Ψ sites. The PIANO website is freely accessible at: http://piano.rnamd.com.